2016
DOI: 10.1039/c6ra03699f
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of nanofunctionalized alginate/methacrylated gelatin hybrid hydrogels

Abstract: We developed the preparation of alginate/methacrylated gelatin (GelMA) hybrid hydrogels functionalized with nanoliposomes encapsulating curcumin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…This tendency was confirmed after 8 h of incubation, and the rate of mass loss was approximately double (39.2% in GelMA-Nanoliposomes hydrogels against 21.0% and 18.3% in pure GelMA and GelMA-Emulsion hydrogels, respectively). This increase can be due to a physical phenomenon, as nanoliposomes incorporation increases pores size and enhances their distribution [ 29 ], which releases a way of privileged access to the collagenase, multiplying by twice the area of access sequences Arg-Gly-Asp (RGD), which are considered matrix metalloproteinase 2 (MMP-2) binding sites. These enzymes can degrade and remodel the extracellular matrix for cell spreading and migration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This tendency was confirmed after 8 h of incubation, and the rate of mass loss was approximately double (39.2% in GelMA-Nanoliposomes hydrogels against 21.0% and 18.3% in pure GelMA and GelMA-Emulsion hydrogels, respectively). This increase can be due to a physical phenomenon, as nanoliposomes incorporation increases pores size and enhances their distribution [ 29 ], which releases a way of privileged access to the collagenase, multiplying by twice the area of access sequences Arg-Gly-Asp (RGD), which are considered matrix metalloproteinase 2 (MMP-2) binding sites. These enzymes can degrade and remodel the extracellular matrix for cell spreading and migration.…”
Section: Resultsmentioning
confidence: 99%
“…can be optimized further by incorporating nanoparticles within the hydrogel. Previous works [ 29 , 30 ] showed that nanoliposomes improve mechanical properties and porosity of the GelMA hydrogels. In order to compare the various properties of GelMA functionalized with lipidic nanoparticles differing by their external surface hydrophilicity and their structure.…”
Section: Introductionmentioning
confidence: 99%
“…Phospholipids are amphiphilic molecules composed of a hydrophilic head and a hydrophobic tail. Their amphiphilic property allows the self-sealing of liposomes, which renders them an ideal delivery system in aqueous media and has various applications in the cosmetic [30], food [31], pharmaceutical [32], and tissue engineering [33,34] fields.…”
Section: Introductionmentioning
confidence: 99%
“…Rahali et al functionalized GelMA hydrogels with naturally derived nanoliposomes and reported that the incorporation of nanoliposomes enhanced the mechanical stability of the functionalized GelMA hydrogels; proven by their higher resistance to twist and shear . Similarly, it was also demonstrated that the incorporation of nanoliposomes within alginate/GelMA hydrogels affected the rheological properties of the formed hydrogels, as well as their mechanical properties . This observation was related to the ability of the alginate–gelatin mixture to tune the mechanical properties of refined architectures.…”
Section: Properties Of Soft Nanoparticle–functionalized Hydrogelsmentioning
confidence: 99%